Monocropping vs mixed cropping systems under a changing climate: Smallholder farmers' perceptions and farm profitability in Eastern Rwanda - Hashakimana Léonidas; Tessema Toru; Niyitanga Fidèle; Mulugeta D. Watabaji; Tadele Bedo Gelete; Hirwa Hubert (Environmental and Sustainability Indicators)
Traditionally, mixed cropping (MxC) has been Rwanda's smallholder farming technology used to sustainably manage farmlands for family subsistence while forming dynamic and climate-resilient agroecosystems. Yet, its significance is overlooked over monocropping (MnC) adopted at dissent since the inception of Crop Intensification Program (CIP) in Rwanda. Thus, this study sought to analyze and compare MnC and MxC systems based on farmers' perceptions and farm profitability in drought-prone areas of Kayonza district in Eastern Province of Rwanda. The farmers' perceptions were assessed using questionnaires, focus group discussions (FGDs), and in-depth group interviews (IDGIs). The farm profitability was assessed using revenue-cost ratio (RCR) analysis. Purposive and multi-stage random sampling techniques were used for selecting sample households (n = 196). The data were analyzed using IBM SPSS software (version 25). Thematic content analysis method and Pearson correlations were used to analyze farmers' perceptions. The binomial logit model was used to determine the effect of the selected determinants on adopting either MxC or MnC. The results show that the majority of the respondents were more involved in MxC during short-rainy and dry seasons (98%) than MnC. Household heads' sex, family size, access to credit services, access to weather and climate information, access to extension services, social group membership, and farm income were highlighted to motivate farmers to adopt MxC systems. The latter was, therefore, shown to be more socio-economically and ecologically beneficial to farmers than MnC under drought conditions as it was chosen and adopted by most smallholder farmers and provided higher on-farm benefits (RCR>4).